The Sacroiliac Joint as a Cause of Pain – Review of the Sacroiliac Joint Morphology and Models for Pain Genesis - Völker, Anna; Steinke, Hanno; Heyde, Christoph-Eckhard (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Introduction In recent years, the sacroiliac joint has become increasingly important as a generator of low back pain with and without pseudo-radicular pain in the legs. Up to 27% of reported back pain is generated by disorders in the sacroiliac joint.Method This review is based on a selective literature search of the sacroiliac joint (SIJ) as a possible pain generator. It also considers the anatomical structures and innervation of the sacroiliac joint.Results The SIJ is a complex joint in the region of the posterior pelvis and is formed by the sacrum and the ilium bones. The SIJ is very limited in movement in all three planes. Joint stability is ensured by the shape and especially by strong interosseous and extraosseous ligaments. Different anatomical variants of the sacroiliac joint, such as additional extra-articular secondary joints or ossification centres, can be regularly observed in CT scans. There is still controversy in the literature regarding innervation. However, there is agreement on dorsal innervation of the sacroiliac joint from lateral branches of the dorsal rami of the spinal nerves S I–S III with proportions of L III and L IV as well S IV. Nerve fibres and mechanoreceptors can also be detected in the surrounding ligaments.Conclusion A closer look at the anatomy and innervation of the SIJ shows that the SIJ is more than a simple joint. The complex interaction of the SIJ with its surrounding structures opens the possibility that pain arises from this area. The SIJ and its surrounding structures should be included in the diagnosis and treatment of back and leg pain. Published literature include a number of plausible models for the sacroiliac joint as pain generator. The knowledge of the special anatomy, the complex innervation as well as the special and sometimes very individual functionality of this joint, enhance our understanding of associated pathologies and complaints.
Keywords: sacroiliac joint; back pain; anatomy of the pelvis